Perlindungan Hukum Terhadap Hak Pemegang Jaminan Gadai Saham - Annisa Oktaviananda Putri (Lex Renaissance, 2020)
This research contains the problem formulation as follow, first, what is the rationale behind the judge's consideration in deciding the share-mortgage case based on the Supreme Court Decision No. 240 PK/Pdt/2006 and the Supreme Court Decision No. 115 PK/Pdt/2007. Second, how the Supreme Court Decision No. 240 PK/Pdt/2006 and the Supreme Court Decision No. 115 PK/Pdt/2007 provide legal protection to the mortgaged share holders. This is a normative legal research with case and legislation approach. The results indicate that there are differences in the outcomes of the Supreme Court Decision No. 240 PK/Pdt/2006 and the Supreme Court decision No. 115 PK/Pdt /2007 in the substance of the similar case. Based on the Supreme Court No. 240 PK/Pdt/2006, the execution of share-mortgage by PT BFI Finance Indonesia Tbk is illegal, while in the Supreme Court Decision No. 115 PK/Pdt/2007 the execution by PT BFI Finance Indonesia Tbk is legal. The difference in the outcomes of the decisions in the substancially similar cases has created legal uncertainty over the protection of PT BFI Finance Indonesia Tbk's rights as a creditor as well as the mortgaged share holder.